2018
DOI: 10.3347/kjp.2018.56.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Tests of IgG and IgM Antibodies and IgG Avidity for Diagnosis of Ocular Toxoplasmosis

Abstract: This prospective study was aimed to detect acute and chronic ocular toxoplasmosis by comparison of anti-Toxoplasma gondii IgM and IgG antibody levels and IgG avidity test. One hundred and seventeen patients with ocular toxoplasmosis (OT) who referred to the Farabi Eye Hospital, Tehran, Iran were included in this study. Of the patients, 77 cases were positive for anti-T. gondii IgG, and 8 cases were positive for anti-T. gondii IgM. IgG avidity test revealed 11, 4, and 102 cases were low, intermediate, and high,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…With the IgG avidity method, the results showed that 98.35% of the samples had high avidity, indicating that ocular toxoplasmosis caused by reactivation of chronic infection of toxoplasma. This is similar to the results by Rahimi-Esboei et al who reported that 87.2% of the cases had high IgG avidity in Iran-Teheran in their prospective study on patients with ocular toxoplasmosis (OT) who referred to the Farabi Eye Hospital, Tehran, Iran [32]. Also our result consistent with the results by Jones et al [33] who showed that 11.7% of their cases in the USA have recently acquired infection and 88.3% were IgG positive/IgM negative, which indicated they had chronic ocular toxoplasmosis.…”
Section: Discussionsupporting
confidence: 90%
“…With the IgG avidity method, the results showed that 98.35% of the samples had high avidity, indicating that ocular toxoplasmosis caused by reactivation of chronic infection of toxoplasma. This is similar to the results by Rahimi-Esboei et al who reported that 87.2% of the cases had high IgG avidity in Iran-Teheran in their prospective study on patients with ocular toxoplasmosis (OT) who referred to the Farabi Eye Hospital, Tehran, Iran [32]. Also our result consistent with the results by Jones et al [33] who showed that 11.7% of their cases in the USA have recently acquired infection and 88.3% were IgG positive/IgM negative, which indicated they had chronic ocular toxoplasmosis.…”
Section: Discussionsupporting
confidence: 90%
“…During October 2018 to July 2019, fifty-six samples including corneal scrapes, contact lenses or its maintenance solution were collected from keratitis patients referred to the Farabi eye teaching hospital, Tehran city, capital of Iran ( Esboei et al, 2019 ; Rahimi-Esboei et al, 2018 ). All clinical samples were inspected by both direct microscopic and culture methods.…”
Section: Methodsmentioning
confidence: 99%
“…Also, molecular methods such as polymerase chain reaction may be useful for the detection of the infection by amplification of conserved sequences of parasite genes (MarĂ­n et al 2018 ). Despite the availability of these laboratory analyses for toxoplasmosis diagnostic, the confirmation of ocular toxoplasmosis is usually clinical and when the clinical examination is not sufficient to confirm its presence, the laboratory diagnostic involves the analyze of ocular fluids (Greigert et al 2019a ; Rahimi-Esboei et al 2018 ; Rahimi Esboei et al 2019 ) using polymerase chain reaction and immunoblot techniques (Greigert et al 2019b ). Thus, there is an interest in finding new markers and predictors of disease useful for ocular toxoplasmosis diagnostics and monitoring, and some routine laboratory tests may be better explored for this purpose.…”
Section: Introductionmentioning
confidence: 99%